2014
DOI: 10.1111/eff.12129
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale, seasonal habitat use and movements of yellow American eels in the St. Lawrence River revealed by acoustic telemetry

Abstract: Large‐scale habitat use and movements of yellow American eels (Anguilla rostrata) from the St. Lawrence River were examined using acoustic telemetry from early summer to late fall in 2010 and 2011. Sixty‐seven eels were tagged, and their passage or presence was recorded using fixed acoustic arrays covering a 400 km distance along the St. Lawrence River and Estuary. Sixty‐four per cent of the 67 tagged eels were detected. Most eels were detected at only one array; the closest to their release location and at se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 41 publications
3
34
0
Order By: Relevance
“…In the present study, early‐season migrating A. dieffenbachii frequently took several weeks to reach Tuatapere, whereas late‐season A. dieffenbachii achieved this in a day or less. This behaviour is similar to the seasonal reduction in transit time noted for A. rostrata (Béguer‐Pon et al, ) and A. anguilla (Aarestrup et al, ). Presumably late‐season eels are under some behavioural pressure to reach the estuarine area within the optimum time of seaward egress.…”
Section: Discussionsupporting
confidence: 86%
“…In the present study, early‐season migrating A. dieffenbachii frequently took several weeks to reach Tuatapere, whereas late‐season A. dieffenbachii achieved this in a day or less. This behaviour is similar to the seasonal reduction in transit time noted for A. rostrata (Béguer‐Pon et al, ) and A. anguilla (Aarestrup et al, ). Presumably late‐season eels are under some behavioural pressure to reach the estuarine area within the optimum time of seaward egress.…”
Section: Discussionsupporting
confidence: 86%
“…These authors also mentioned a post-release downstream movement of 4,300 m for an individual that returned 12 h later to establish a refuge 640 m downstream of the release site. This rhythmic pattern of activity was recently confirmed for the American eel Anguilla rostrata [38].…”
Section: Post-release Movementssupporting
confidence: 61%
“…Numerous telemetric studies have been carried out on the Atlantic eels A. anguilla and A. rostrata and the New Zealand eels Anguilla australis and Anguilla dieffenbachii. Furthermore, while most eels overwinter in the same habitat as the one they occupy at other times of the year (Ovidio et al, 2013), some move from brackish water estuaries to freshwater rivers to overwinter (Béguer-Pon et al, 2015;Hedger et al, 2010). These studies have shown that yellow eels are principally nocturnal (Hedger et al, 2010;Jellyman & Sykes, 2003;Walker et al, 2014) and have decreased activity during winter.…”
mentioning
confidence: 98%
“…They have described the movements and time and space utilisation of eels in rivers (Jellyman & Sykes, 2003;Ovidio, Seredynski, Philippart, & Nzau Matondo, 2013) and estuarine habitats (Béguer-Pon et al, 2015;Hedger, Dodson, Hatin, Caron, & Fournier, 2010;Parker, 1995;Simpfendorfer, Olsen, Heupel, & Moland, 2012;Thibault, Dodson, & Caron, 2007;Walker, Godard, & Davison, 2014). Numerous telemetric studies have been carried out on the Atlantic eels A. anguilla and A. rostrata and the New Zealand eels Anguilla australis and Anguilla dieffenbachii.…”
mentioning
confidence: 99%
See 1 more Smart Citation